PENGARUH TINGKAT KECUKUPAN MODAL, EFISIENSI OPERASIONAL, RISIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERBANKAN SYARIAH YANG TERDAFTAR DI OJK PERIODE 2015-2019 - Lita Permata Sari (Relawan Jurnal Indonesia, 2020)
This study aims (1) to determine the effect of Capital Adequacy Levels (CAR), Operational Efficiency (OEOI), Credit Risk (NPF) and Liquidity (FDR) partially on Profitability (ROA), (2) to determine the effect of the effect of Capital Adequacy Levels (CAR), Operational efficiency (OEOI), Credit risk (NPF) and Liquidity (FDR) simultaneously on Profitability (ROA), and (3) to determine which of the effect of Capital Adequacy Levels (CAR), Operational efficiency (OEOI), Credit risk (NPF) and Liquidity (FDR) has the most influence on Profitability (ROA) in Islamic banking registered with the OJK for the period 2015-2019. The method used in this research is quantitative method. The result of research is multiple linear regression equation Y = 21,756 + 0,11X1 - 0,349X2 + 0,507X3 + 0,117X4 + e. Partially CAR has no significant effect on the ROA, OEOI has a significant negative effect on the ROA, NPF and FDR has a significant positive effect on the ROA. Simultaneously CAR, OEOI, NPF and FDR partially to ROA. The most dominant variable in this research is OEOI with value -13,352. The predictive ability of these variables on ROA in this study was 89,1%, while the remaining 10,9% is influenced by other variables not included in this study.